2016
DOI: 10.1371/journal.pone.0167379
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Inhibitory Allosteric Site in p38α

Abstract: In the present study, we report the discovery of a novel allosteric inhibitory site for p38α, a subclass of the mitogen-activated protein kinases (MAPK) family. The putative site was discovered after inspection of the crystallographic structure of the p38α-MK2 complex. MK2 (MAPK-activated protein kinase 2) is an interesting protein playing a dual role as modulator and substrate of p38α. This intriguing behavior is due to the ability of the two proteins to form distinctive heterodimers when p38α is phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 29 publications
4
16
0
Order By: Relevance
“…The chemical structures of the six compounds were found to displace the radioligand used in the binding assays by more than 15%, as listed in Table 1 . These results yielded a success rate of about 50%, as found in other cases [ 39 , 40 ]. Table 1 also lists the results of radioligand displacement experiments for the BB1R and BB2R, suggesting that the ligands are BB1R selective.…”
Section: Resultssupporting
confidence: 74%
“…The chemical structures of the six compounds were found to displace the radioligand used in the binding assays by more than 15%, as listed in Table 1 . These results yielded a success rate of about 50%, as found in other cases [ 39 , 40 ]. Table 1 also lists the results of radioligand displacement experiments for the BB1R and BB2R, suggesting that the ligands are BB1R selective.…”
Section: Resultssupporting
confidence: 74%
“…Finally, the procedure also identifies an allosteric site recently reported by this laboratory, located between the ACE motif of the activation loop, the αEF helix, the N-terminal end of the αG helix, and part of the N-terminal segment of the activation. 57 Additionally, ten prospective binding sites, not previously described for the p38α protein or other MAP kinases named NP1 to NP10, are shown in Figure 6b. The NP1 site is located at the back of the beta sheets between the ends N-terminal and C-terminal, which is in an area with a high flexibility.…”
Section: ■ Results and Discussionmentioning
confidence: 85%
“…MD simulations permitted definition of pharmacophoric features of small peptide inhibitors derived from sequence of MK2. Subsequent virtual screening study resulted in first small molecule allosteric inhibitor for identified binding site (Gomez-Gutierrez et al, 2016). Cournia et al verified existence of allosteric site on human PI3Kα previously described in murine PI3Kα using combination of FTMap, MD, and in vitro assays.…”
Section: Molecular Dynamics-based Approaches To Investigate Allosterymentioning
confidence: 90%